Packaging investigation of optoelectronic devices*Project supported by the National High Technology Research and Development Program of China (Nos. 2013AA014201, 2013AA014203) and the National Natural Science Foundation of China (Nos. 61177080, 61335004, 61275031). (October 2015) - Zhang 张, Zhike 志珂; Liu 刘, Yu 宇; Liu 刘, Jianguo 建国; Zhu 祝, Ninghua 宁华
Abstract: Compared with microelectronic packaging, optoelectronic packaging as a new packaging type has been developed rapidly and it will play an essential role in optical communication. In this paper, we try to summarize the development history, research status, technology issues and future prospects, and hope to provide a meaningful reference.